2021
DOI: 10.3389/fnut.2021.795491
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Adaptive Laboratory Evolution Strategy to Enhance Docosahexaenoic Acid Synthesis in Oleaginous Thraustochytrid

Abstract: Thraustochytrid is a promising algal oil resource with the potential to meet the demand for docosahexaenoic acid (DHA). However, oils with high DHA content produced by genetic modified thraustochytrids are not accepted by the food and pharmaceutical industries in many countries. Therefore, in order to obtain non-transgenic strains with high DHA content, a two-stage adaptive laboratory evolution (ALE) strategy was applied to the thraustochytrid Aurantiochytrium sp. Heavy-ion irradiation technique was first used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…They found that stress conditions such as low temperature (Ma et al, 2017), low or high dissolved oxygen (Sun et al, 2016;Heggeset et al, 2019) and nitrogen starvation (Chen et al, 2022) could stimulate the accumulation of intracellular lipids. Laboratory domestication and phased cultivation strategies (Wang et al, 2021a;Chen et al, 2022) have been developed. Additionally, the inclusion of lipase inhibitors (Orlistat) (Ma et al, 2021), antioxidants (Zhang et al, 2020) and plant hormones (Yu et al, 2016) in the culture medium can influence PUFAs metabolism and promote lipid accumulation.…”
Section: Ecological Insights: Unraveling the Compositional Complexity...mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that stress conditions such as low temperature (Ma et al, 2017), low or high dissolved oxygen (Sun et al, 2016;Heggeset et al, 2019) and nitrogen starvation (Chen et al, 2022) could stimulate the accumulation of intracellular lipids. Laboratory domestication and phased cultivation strategies (Wang et al, 2021a;Chen et al, 2022) have been developed. Additionally, the inclusion of lipase inhibitors (Orlistat) (Ma et al, 2021), antioxidants (Zhang et al, 2020) and plant hormones (Yu et al, 2016) in the culture medium can influence PUFAs metabolism and promote lipid accumulation.…”
Section: Ecological Insights: Unraveling the Compositional Complexity...mentioning
confidence: 99%
“…are permitted for use as nutritional additives, but not whole cells. Moreover, oils with high DHA content produced from genetically modified thraustochytrids are not accepted by the food and pharmaceutical industries in many countries (Wang et al, 2021a). Upon the European Commission's request, the European Food Safety Authority (EFSA) Panel on Nutrition, Novel Foods and Food Allergens (NDA) evaluated the safety of S. sp.…”
Section: Harnessing Thraustochytrids For Nutraceutical and Functional...mentioning
confidence: 99%
“…Recently, the role of adaptative lab evolution as a non-genetic approach to improve lipid (especially DHA) accumulation [ 11 ] and introduction of chemical modulators in the fermentation medium have been proposed to improve lipid yields [ 7 , 12 ]. Low-molecular-weight compounds such as propyl gallate [ 7 ], butanol [ 13 ], ascorbic acid [ 14 ], naphthoxyacetic acid (BNOA) [ 12 ] and phytohormones, such as kinetin (KIN), jasmonic acid (JA) and gibberellic acid (GA) [ 15 ], and sesamol [ 16 ], when added to the fermentation medium, could enhance lipid production with reference to polyunsaturated fatty acids (DHA, etc.).…”
Section: Introductionmentioning
confidence: 99%